TRADISI QUNUT DALAM SHALAT MAGHRIB DI PONDOK PESANTREN WAHID HASYIM YOGYAKARTA (Studi Living Hadis) - Siti Qurrotul Aini (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2016)
Living hadis tradition commonly found in Indonesian muslim practice of religiousity. To mention some are tradition of reading Qunut in subuh prayer, but this article found Qunut which is read during maghrib prayer at an-Najah and al-Hikmah boarding house, of Pondok Pesantren Wahid Hasyim, Yogyakarta. Although lots of santri (students) were lack of basic knowledge about dalil of this Qunut shalat Maghrib practice, but they realized that the practice was in line to Islamic basic teaching, as what Nabi has taught us. This paper underlines the how and why students elaborate the practice as part of their daily life.